PMO-256 The reality of the tolerance and efficacy of oral iron in patients with inflammatory bowel disease (IBD). (28th May 2012) - Beal, F; Lugg, S; Rattehalli, D; Tselepis, C; Iqbal, T
Abstract : Introduction: Iron deficiency anaemia (IDA) is the most common complication of Inflammatory Bowel Disease (IBD) and impacts negatively on patients' quality of life. The aim of this audit was to explore the use and tolerability of oral iron supplementation in IBD practice. Methods: We used a patient directed questionnaire aimed at adult IBD outpatients over a 7-week period at the Queen Elizabeth Hospital. The use of oral iron therapy was ascertained in patients treated over 20 years. Patients were asked about the type of iron taken, dosing frequency, duration, side-effects and completion of therapy. We calculated the number of patients whose anaemia had resolved and where the data were available, the efficacy of treatment was determined by the mean change in haemoglobin (Hb) from baseline. Results: 91 IBD patients who received iron were surveyed, (62 Crohn's disease, 27 ulcerative, 2 microscopic colitis). All received oral iron (73 ferrous sulphate, 15 ferrous fumarate and 3 ferrous gluconate) and 17 also received intravenous (IV) iron. There were 56 females and 35 males. Variable dosing regimens were followed: 31.5% taking iron once, 37% twice and 31.5% three times daily. Although 69% patients were able to complete the course of oral iron, 31% had to abort treatment due to intolerance, which was unrelated to dose frequency. Only 35 patients (38%) were able to complete their intended course of oral iron without any side effects. Of these patients, the baseline Hb (mean 11.1 g/dl, range 8.9–13.3) returned to reference baseline in only 51% patients, with average Hb change 1.43 (range −0.7–4.7). Side effects were reported in 52% patients who received oral iron, including nausea and vomiting (21%), abdominal pain (19%), constipation (19%) and diarrhoea (18%.) However, despite side effects the average duration of treatment in this cohort was 10.3 months (range 0.03–156), 19.3 months (range 1–240) in patients without side effects and 5.2 months (range 0.03–36) in intolerant patients who had to cease treatment. No adverse effects were reported in the 17 who received IV iron. Conclusion: Although oral iron is a cheap and convenient treatment for IDA, over half of the patients in this study experienced gastro-intestinal side effects, a large proportion remained anaemic and for many the treatment course was long. Despite iron therapy IDA prevalence in this group remains high and it seems the efficacy of oral iron treatment is poor in this setting. We propose that prescription of iron therapy in IBD patients should be trialled with a defined duration of treatment and a target end point Hb. Those who fail to tolerate or do not respond adequately should consider an alternative form of iron therapy such as IV iron. Competing interests: None declared.